FACTORS AFFECTING CHANGES IN THE POPULATION OF SOWS IN POLAND : REGIONAL ANALYSIS - Benedykt Pepliński (Acta Scientiarum Polonorum. Oeconomia, 2016)
Since 2008 there has been a deep crisis in the production of pork in Poland. It has been especially noticeable in the decreasing population of pigs, especially sows. The aim of the article was to analyze the factors affecting changes in the sow population in Poland and in individual voivodeships. The period under investigation ranged from 2001 to 2014. The study was based on the results of a model farm with a semi-closed cycle production system. The farm sold 3836 porkers in 2011. The analysis proved that there was a high correlation between the cost-effectiveness of porker and piglet production and the sow population level at the end of the following year. In individual voivodeships there was low dependence between changes in the sow population and the cost-effectiveness of porker and piglet production. However, there was a high correlation between the average sow population in individual voivodeships and the number of piglets farrowed by one sow per year.